Prevalencia de Brucella Canis y Factores asociados a Caninos Domésticos (canis familiaris) en el Barrio San Pedro de Teneria de la Parroquia Pastocalle. - Chicaiza Pimboza, Jorge Luis (2019)
The present investigation was carried out with the objective of establishing the prevalence of Brucella canis and associated factors to a sample of the canine population belonging to the San Pedro de Teneria neighborhood of Pastocalle parish, in Latacunga canton, province of Cotopaxi, Ecuador. The investigation was carried out in 75 domestic canines, from which blood samples were obtained, and transported to the CAREN Faculty from UTC laboratory, where the brucella Ab Test Kit rapid diagnostic test were performed, to determine the percentage of canines infected with brucella canis, according to age. Surveys and clinical files were also carried out, with data provided by the owners, with which the factors associated with canine brucellosis were established, among the most important data were: the number of bitches that had presented abortions or any signs of malignancy or pathology within the period of gestation, as well as the dogs that have had at their disposal the consumption of dairy products from cattle, environment where the domestic canine lives, the availability of food and coexistence with other species. Once the results were obtained by Kit Rapid Test in all the blood samples, we proceeded to tabulate the data and to relate, analyze them according to the clinical file and questionnaire of each of the 75 domestic canines, in order to establish the prevalence and the factors associated with brucellosis in the canines under study. Once the tabulated data of the surveys were correlated with those of the laboratory, finally, the results obtained from the research were disseminated to the inhabitants of barrio Teneria from San Juande Pastocalle parish, thus achieving safeguarding the public health of the area inhabitants of the area inhabitants of our research against a zoonotic disease that is brucellosis.